Performance evaluation of energy-efficient Beaconless Routing Protocol for ML-MAC grid topology in Wireless Sensor Network - Akter, Mahmuda (Kulliyyah of Engineering International Islamic University Malaysia, 2018)
IEEE802.15.4 is a concrete challenge to provide energy-efficient communication for numerous monitoring applications in Wireless Sensor Networks (WSNs) due to the enhancements of Medium Access Control (MAC) layer specifications and topology-based routing protocols. In contention-based conventional MAC layer protocols are considered as the single-layer protocols, where the static listen or sleep scheduling technique is used. These protocols keep the channels in unwanted idle listening mode during the variation of traffics. Hence, increases the channel congestion, packets collisions and consumes more battery energy. However, to overcome these issues, some researchers propose Multi-Layer (ML-MAC) concept to control congestion and packet collisions but still consuming much unwanted energy due to routing protocols. Conventional flooding-based routing protocols broadcast beacon frame or “hello” message periodically to identify the optimal path to forward sensing data from source sensor to sink node resulting sensor nodes receive redundancy data from other nodes and consumes more energy in terms of both transmissions and receptions. This thesis integrates a Beaconless Routing Protocol (BLR) in ML-MAC concept for high-density grid topology which eliminates the broadcasting redundancy and conserves battery energy in sensor network. The performance evaluation of BLR-ML-MAC protocol for high-density grid topology has been carried out and benchmarked it with the conventional Ad-hoc On demand Distance Vector (AODV) ML_MAC routing protocol. The simulation results show that the energy consumption, network lifetime, jitter, end-to-end delay and throughput in the proposed scheme are significantly improved about 57.14%, 37.10%, 26.27%, 7.12% and 27.28% respectively compared to benchmark scheme.